2021
DOI: 10.1186/s43055-020-00378-w
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver agreement of Prostate Imaging–Reporting and Data System (PI-RADS–v2)

Abstract: Background A retrospective study was conducted on 71 consecutive patients with suspected prostate cancer (PCa) with a mean age of 56 years and underwent mp-MRI of the prostate at 3 Tesla MRI. Two readers recognized all prostatic lesions, and each lesion had a score according to Prostate Imaging–Reporting and Data System version 2 (PI-RADS-v2). Purpose of the study To evaluate the interobserver agreement of PI-RADS-v2 in characterization of prostati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
(91 reference statements)
0
5
0
Order By: Relevance
“…The time delay between the TRUS-guided biopsy and MR imaging was 6 weeks. The patients in this study were part of a previous study to analyze the inter-observer agreement of PI-RADS v2 [7] .…”
Section: Exclusion Criteriamentioning
confidence: 99%
See 3 more Smart Citations
“…The time delay between the TRUS-guided biopsy and MR imaging was 6 weeks. The patients in this study were part of a previous study to analyze the inter-observer agreement of PI-RADS v2 [7] .…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…1) on all sectors of the tumor, and the mean values of the tumor were considered. The radiologist used T2WI, DWI, and Dynamic MR to classify the prostate lesion according to PI-RADSv2 [7] . The MR images divided the prostate into 6 zones into both sides at the base, mid part, and apex of the gland to simulate the systematic TRUS biopsies taken from different regions of the prostate.…”
Section: Image Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…However, due to limitations such as suboptimal inter-reader responsibility, a high false-negative rate for the lower PI-RADS assessment category, and a lower detection rate for TZ prostate cancer (TZPC) than for PZ prostate cancer, the updated PI-RADS Version 2.1 (PI-RADS v2.1) was developed in 2019 [9][10][11]. Several studies suggested that PI-RADS v2.1 is preferable for evaluating transition-zone lesions and showed that it provided comparable interreader agreement [12][13][14]. One study reported that typical benign prostatic nodules in the TZ were downgraded, but there were no significant changes in the number of positive and negative MRI results identified using PI-RADS v2.1 [15].…”
Section: Introductionmentioning
confidence: 99%